Prevalence and factors associated with sugar-sweetened beverage intake among undergraduate students in a public university in Malaysia - Ahmad, Norliza; Md Zuki, Muhammad Afiq; Azahar, Nur Azilah; Khor, Boon Han; Minhat, Halimatus Sakdiah (Asian Network for Scientific Information, 2019)
Background and Objective: Reduction in sugar-sweetened beverage (SSB) intake is one of the World Health Organizationʼs recommendations to reduce noncommunicable disease burden. The prevalence of SSB consumption was highest among young adults. The objective of this study was to examine the prevalence of SSBs and factors associated with their consumption among undergraduate students in a residential area in one of the public universities in Malaysia. Materials and Methods: This was a cross-sectional study using a pretested, validated, self-administered questionnaire on sociodemographic characteristics, level of knowledge, family history of diabetes and lifestyle pattern. High SSB intake was defined as an intake of three or more SSBs in a day. Height and weight were measured and body mass index (BMI) was calculated. Results: A total of 401 students responded with a response rate of 77.9%. The mean age was 21.3 years (95% CI = 21.20-21.48). The prevalence of at least once daily SSB intake and high SSB intake was 89.3 and 53.3%, respectively. Predictors for high SSB consumption were being men (OR = 2.19, 95% CI 1.07-4.48), having a low family income (OR = 2.05, 95% CI = 1.12-3.76) and having a high level of fast food intake (OR = 1.82, 95% CI = 1.03-3.22). Conclusion: The prevalence of SSB consumption was high among undergraduate students. Innovative health promotion strategies need to be implemented to reduce SSB consumption.